Pengaruh Integrasi Nilai Tafsir Tarbawi Terhadap Pembentukan Kepribadian Moral Peserta Didik - Mirza, Iskandar; Solihah, Rika (Penerbit Widina, Widina Media Utama, 2025)
“Tafsir Tarbawi” in the formation of students' moral personality comes from the need to instill strong Islamic moral and ethical values in students. In the context of Islamic education, Tafsir Tarbawi is a method of interpreting the Qur'an that focuses on educational values and character development. Through this approach, the moral values contained in the verses of the Qur'an are elaborated and used as the basis for the formation of noble morals in learners. Tafsir Tarbawi aims to introduce learners to ideal role models (uswatun hasanah) in Islamic teachings. These examples are found in the stories of the prophets, companions, and verses of the Qur'an that discuss ethics and noble personalities. With this approach, Tafsir Tarbawi acts as a tool to internalize Islamic values in students, in order to form a person who is not only intellectually intelligent but also has good morals. The study of Tafsir Tarbawi helps learners understand how the teachings of the Qur'an should be applied in daily life. It helps them internalize moral values such as honesty, patience, perseverance and responsibility, all of which are essential in personality formation. This process also teaches learners to take the Qur'?n as a guide to life in interacting with others, making moral decisions, and living life in an Islamic manner. Overall, Tafsir Tarbawi emphasizes that the main goal of education in Islam is the formation of human beings who are noble and pious to Allah, who are not only able to be good individuals, but also able to provide examples and benefits for others.ABSTRAK